Antimicrobial use in smallholder livestock systems in Ethiopia (AMUSE) - Wieland, Barbara; Alemu, Biruk; Dione, Michel; Magnusson, Ulf; Amenu, Kebede; Desta, Hiwot; Alemayehu, Gezahegn (International Livestock Research Institute, 2023)
The aim of this project was to develop a tool (AMUSE) to understand knowledge, attitudes and practices of smallholder farmers regarding antimicrobial use, antimicrobial resistance and the presence of residues of antimicrobials. It also documents drivers of behaviour for AMU, identifies sources of counterfeit or poor-quality medicines. The tool can be used for different production systems and species in different countries to be able to collate and compare data of different sources.